2008
DOI: 10.1097/ta.0b013e31816275b0
|View full text |Cite
|
Sign up to set email alerts
|

Trauma Training in Simulation: Translating Skills From SIM Time to Real Time

Abstract: : A trauma curriculum incorporating simulation shows promise in developing crisis management skills that are essential for evaluation of critically injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 21 publications
2
69
0
4
Order By: Relevance
“…Previously, its utility had been proven in military environments, aeronautics, and the management of accidents or natural disasters, but its application in medicine has clashed with the concept of traditional teaching based on the transmission of theory and learning by "imitation and repetition" on the patient. With initial misgivings having been overcome, simulation in medicine has offered results similar to those obtained in other disciplines [2][3][4][5].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previously, its utility had been proven in military environments, aeronautics, and the management of accidents or natural disasters, but its application in medicine has clashed with the concept of traditional teaching based on the transmission of theory and learning by "imitation and repetition" on the patient. With initial misgivings having been overcome, simulation in medicine has offered results similar to those obtained in other disciplines [2][3][4][5].…”
Section: Introductionsupporting
confidence: 56%
“…Numerous studies in recent years have demonstrated that training through simulation and debriefing is an effective tool for improving performance in real clinical situations [2][3][4][5]. Other studies, in contrast, have not found differences between traditional methods and simulationbased methods [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have demonstrated that use of simulation-based learning methodologies enhances performance in both real-life clinical situations and simulated resuscitations, [107][108][109][110] although a few studies have found no differences when compared to standard or other nonsimulated training. 111 …”
Section: Structure Of Educational Programs To Teach Neonatal Resuscitmentioning
confidence: 99%
“…Use of simulation as an adjunct to traditional education methodologies may enhance performance of healthcare professionals in actual clinical settings (LOE 1 163 ; LOE 3 164 ) and simulated resuscitations (LOE 1 165 ; LOE 2 166 ). Some studies did not show any difference in performance between standard training and simulation training in a clinical setting (LOE 1 167 ) or using other means of evaluation (LOE 1 168 ).…”
Section: Consensus On Sciencementioning
confidence: 99%